The Effect of Traditional Ripening Methods on Weight Loss and Sensory Characteristics of Sapodilla Fruit: The Effect of Traditional Ripening Methods on Weight Loss and Sensory Characteristics of Sapodilla Fruit - Ihsan, Fikratul; Anggraini, Anna; Masyitah, Masyitah; Alhaviz, Alhaviz (Rumah Jurnal, 2025)
-Sapodilla is a climacteric fruit that widely cultivated in tropical areas, so proper post-harvest handling is required. Natural ripening results in uneven levels of fruit ripeness. The proper ripening techniques can control fruit ripeness uniformly. This study aims to known the effect of traditional ripening methods on the percentage of weight loss and physical changes, including color and texture of sapodilla fruit. The ripening techniques used were: 1. sunlight, 2. soaked in rice, 3. wrapped in linen, and 4. wrapped in paper. Ripening was carried out for 5 days, and observations were made on days 0, 1, 3, and 5 for weight loss, color, and texture. Based on the results, the traditional ripening method significantly affected the percentage of fruit weight loss and affected color and texture during the ripening process. The rate of weight loss on the fifth day of observation from highest to lowest was sunlight treatment (10.68%), linen (10.31%), paper (9.31%), and rice (8.12%). Changes in color and firmness began to occur on the first day of ripening using linen and rice. The linen and rice ripening treatment produced the sapodilla with the fastest ripening rate, as observed in the color and firmness of the sapodilla fruit after five days of ripening.